Assessing the adoption of specialized rice production technology in selected towns of Nueva Ecija - Mercado, Thomas Jahson S; Buenavista, Mari Joy M; Pascual, Marife DT; Badua, Aldrin E (Asian Journal of Agriculture and Rural Development, 2025)
This study assesses the adoption of special rice production (SPR) technology among rice farmers in selected towns of Nueva Ecija. Specifically, it examined the influence of socio-demographic factors and extension services on the perceived attributes of the technology. Using a survey research design, interviews were guided by a semi-structured questionnaire. Farmers showed strong positive perceptions and high adoption of special rice production (SPR). Adoption was significantly influenced by age, farming experience, institutional support, and favorable technology traits. Regression analysis indicated that gross income and water source positively impacted adoption, while farm size, training services, and perceived relative advantage had negative effects. The extension services from CLSU play a significant role in facilitating the adoption of SPR technology. However, challenges related to the costs and complexities of the technology, as well as unexpected negative effects on training, highlight areas for improvement. Future efforts should focus on addressing these challenges, ensuring that economic and practical barriers do not hinder the widespread adoption and successful implementation of special purpose rice production technology. This study provides insights for policymakers and stakeholders to develop strategies for wider adoption of SPR technology.